Spatial apodization of femtosecond laser inscribed fibre Bragg gratings with arbitrary profile - Kalli, Kyriacos; Ιωάννου, Ανδρέας (My University, 2023)
The fabrication of plane-by-plane femtosecond (fs) laser apodized fibre Bragg gratings (FBG) are demonstrated via a fully customizable and controlled inscription that can realize any desired apodized profile, offering >30dB side lobe suppression ratio.